Properties of Orai1 mediated store-operated current depend on the expression levels of STIM1 and Orai1 proteins - Scrimgeour, N (Blackwell Science Inc, 2009)
Two cellular proteins, stromal interaction molecule 1 (STIM1) and Orai1, are recently discovered essential components of the Ca(2+) release activated Ca(2+) (CRAC) channel. Orai1 polypeptides form the pore of the CRAC channel, while STIM1 plays the role of the endoplasmic reticulum Ca(2+) sensor required for activation of CRAC current (I(CRAC)) by store depletion. It is not known, however, if the role of STIM1 is limited exclusively to Ca(2+) sensing, or whether interaction between Orai1 and STIM1, either direct or indirect, also defines the properties of I(CRAC). In this study we investigated how the relative expression levels of ectopic Orai1 and STIM1 affect the properties of I(CRAC). The results show that cells expressing low Orai1 : STIM1 ratios produce I(CRAC) with strong fast Ca(2+)-dependent inactivation, while cells expressing high Orai1 : STIM1 ratios produce I(CRAC) with strong activation at negative potentials. Moreover, the expression ratio of Orai1 and STIM1 affects Ca(2+), Ba(2+) and Sr(2+) conductance, but has no effect on the current in the absence of divalent cations. The results suggest that several key properties of Ca(2+) channels formed by Orai1 depend on its interaction with STIM1, and that the stoichiometry of this interaction may vary depending on the relative expression levels of these proteins.